Experimental analysis on different runner blades on the vortex performance - Chai Shun Ji (2022)
This thesis writing aim is to design skewed blade profile of the vortex turbine based on the simulation analysis to determine whether it has better efficiency than flat and curved turbine. This is done through experimental analysis for different runner blades on vortex performance. Validation process was first carried out by mesh independent analysis through ANSYS CFX to determine whether there are differences between experimental and simulation results in terms of water vortex height generated. The design of skewed blade is developed by using flow velocity inside vortex that extract from simulation result using horizontal line technique. The data will then convert to a set of coordinates system that will be used to design blade profile. The number of blades used for blade design is 5 blades which will produce the highest efficiency. Experimental analysis was then carried out using three different types of turbine blade which is flat, curved and skewed turbine to determine their vortex performance in terms of power output and efficiency respectively. The final result for this research is that the curved turbine has both the highest power output and efficiency as compared to flat and skewed turbine. This showed that the curved turbine is the best choice for better vortex performance in water generation system.